Screening of Burkholderia spp. from oil palm plantation with antagonistic properties against Ganoderma boninense - YURNALIZA YURNALIZA; DITA ISNAINI RAMBE; LISTRA SARIMUNGGU; MEYLISA PURBA; ISNAINI NURWAHYUNI; SOVIA LENNY; ANISA LUTFIA; ADRIAN HARTANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Yurnaliza. Rambe DI, Sarimunggu L, Purba M, Nurwahyuni I, Lenny S, Lutfia A, Hartanto A. 2020. Screening of Burkholderia spp. from oil palm plantation with antagonistic properties against Ganoderma boninense. Biodiversitas 21: 3431-3437.  Burkholderia spp. are ubiquitous diazotrophic bacteria within ?-Proteobacteria group, known for its occurrence in variety of niches from aquatic to terrestrial habitats and as endophytes. Beneficial strains of Burkholderia have been reported as plant growth-promoting rhizobacteria or as antagonistic bacteria against phytopathogenic fungi. This study evaluated the potential of multiple strains of Burkholderia spp. recovered from three ecological niches, such as rhizosphere, humus soil, and root endophytes of oil palm plantations in North Sumatra to suppress the growth of basal stem rot causative agent in oil palm (Elaeis guineensis Jacq.) by Ganoderma boninense Pat. The antagonistic isolates were identified on the basis of molecular identification using 16S rDNA sequence (27F–1462R), revealing twelve isolates (48%) as members of Burkholderia cepacia complex (Bcc), with other minor genera, such as Chitinophaga, Klebsiella, Mycobacterium, Paenibacillus, Rhizobium, Serratia, Stenotrophomonas, and Xanthomonas. The antagonistic activities as expressed in the percentage inhibition of radial growth (PIRG) against G. boninense were considerably potential with the highest percentage of 55%. In comparison, the crude extract (MeOH, EtOAc) was also tested against G. boninense colonies showing PIRG from 0 to 38%. Majority of isolates did not show any visible chitinolytic activity based on plate assay, in exception to B. contaminans RC02 while most of them were producers of glucanase. The collection of indigenous Burkholderia spp. originating from North Sumatran oil palm plantations, i.e. B. cepacia, B. contaminans, B. metallica, and B. stagnalis may then be considered as potential biocontrol agents against G. boninense based on their antagonistic activities, antifungal properties, and hydrolytic enzyme activities.